2019
DOI: 10.5194/hess-23-2665-2019
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting rainfall-runoff characteristics of floods in desert and Mediterranean basins

Abstract: Abstract. Catchment-scale hydrological studies on drylands are lacking because of the scarcity of consistent data: observations are often available at the plot scale, but their relevance for the catchment scale remains unclear. A database of 24 years of stream gauge discharge and homogeneous high-resolution radar data over the eastern Mediterranean allows us to describe the properties of floods over catchments spanning from desert to Mediterranean climates, and we note that the data set is mostly of moderate i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 80 publications
2
45
0
Order By: Relevance
“…Both factors had a combined effect on the generation of high Qmax values as shown by the significant correlation observed between Ptot and Q0 and Qmax. The role of wet conditions over Qmax also was observed in other Mediterranean catchments where antecedent precipitation correlated significantly with Qmax [14,16,70]. (Table 2).…”
Section: Rainfall-runoff Relationship At Es Fangar Catchmentsupporting
confidence: 59%
See 1 more Smart Citation
“…Both factors had a combined effect on the generation of high Qmax values as shown by the significant correlation observed between Ptot and Q0 and Qmax. The role of wet conditions over Qmax also was observed in other Mediterranean catchments where antecedent precipitation correlated significantly with Qmax [14,16,70]. (Table 2).…”
Section: Rainfall-runoff Relationship At Es Fangar Catchmentsupporting
confidence: 59%
“…Spatial variability of runoff generation is also elucidated in the catchment hydrological response as a combination of rainfall distribution [16] and runoff-contribution areas [17]. Under this context, river connectivity is conceptualized as a continuum from fully connected to disconnected over diverse temporal and spatial scales in the different compartments of a catchment [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, our dataset comprises events of different characteristics: local and intense, as well as widespread; rainfall triggering mechanisms and potential hydrologic impact can be quite different. Zoccatelli et al (2019) observed a relatively high correlation between rain depths over a catchments and unit peak discharge in catchment areas ranging between 13-1232 km 2 of Mediterranean and desert environments in the EM. In arid and semi-arid catchments, high correlation was reported between the storm rain core, defined as the largest hourly intensity over a 9 km 2 area in the catchment, and the unit peak discharge.…”
Section: Multiple Duration Hpes and Their Relation To Flash Floodsmentioning
confidence: 82%
“…This archive was previously used for a series of studies focusing on high intensity precipitation, such as precipitation frequency analysis Marra and Morin, 2015), floods (Rinat et al, 2018;Zoccatelli et al, 2019), and characterisation of convective rain cells (Belachsen et al, 2017;Peleg et al, 2018). Few issues potentially affecting the QPE should be mentioned.…”
Section: Weather Radar Datamentioning
confidence: 99%
“…Moreover, analysing the spatial variation between GS stations helps understand how precipitation extremes can be changed within different climatic zones, even in small areas. As shown in Figure 1, GS classified into three climatic zones; hot‐summer Mediterranean (Csa) in the North: hot semi‐arid (BSh) in the middle and the hot desert (BWh) in the extreme southern part (Peel et al ., 2007; Zoccatelli et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%